The anthropological consequences of the evolution of empiricism - Misztal, Dawid (Hybris, 2012)
The text examines methodological consequences of anti-metaphysical turn of British empiricism in the field of anthropology. I argue that this shift reinforces anthropology in its descriptive and interdisciplinary form, because destruction of metaphysically grounded subjectivity carried out in the course of evolution of empiricism provides epistemological legitimization of the idea of anthropological research as morally neutral and religiously indifferent procedure. In the final part of the article the difficulties caused by application of this new methodology are emphasized.